2020
DOI: 10.3892/ol.2020.11663
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid transcription factor 1 and p63 expression is associated with survival outcome in patients with non‑small cell lung cancer treated with erlotinib

Abstract: While erlotinib is primarily administered to patients with non-small cell lung cancer with sensitizing epidermal growth factor receptor (EGFR) mutations, it is also prescribed to patients with wild type (wt) EGFR in higher lines of treatment. However, there is no predictive marker for erlotinib efficacy in patients with EGFR wt. Certain immunohistochemical (IHC) parameters, including thyroid transcription factor 1 (TTF1) and p63, have been reported to indicate predictive power in patients with EGFR wt. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…TP63 was identified as a differentially expressed gene (DEG) in cancer cell lines that acquired gefitinib resistance, and CSTA is one of the top 10 hub genes in a network of DEGs for gefitinib resistant cancer cell line [ 32 ]. TP63 expression is associated with survival outcomes in patients with NSCLC, treated with erlotinib [ 33 ]. MDM2 is a novel biomarker and treatment target for NSCLC and confers primary resistance to first-generation EGFR-TKIs induced by MDM2 amplification in NSCLC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…TP63 was identified as a differentially expressed gene (DEG) in cancer cell lines that acquired gefitinib resistance, and CSTA is one of the top 10 hub genes in a network of DEGs for gefitinib resistant cancer cell line [ 32 ]. TP63 expression is associated with survival outcomes in patients with NSCLC, treated with erlotinib [ 33 ]. MDM2 is a novel biomarker and treatment target for NSCLC and confers primary resistance to first-generation EGFR-TKIs induced by MDM2 amplification in NSCLC [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TTF1 positivity staining were strongly correlated with the presence of EGFR mutations (p < 0.001) and TTF-1 negativity to be a good predictor of EGFR wt mutations [32]. The results of the Svaton et al study suggested that patients with EGRF wt lung ADs and lack of TTF-1 expression to have significantly lower PFS and OS, and TTF1 expression may be useful predictors of TKIs efficacy in patients with EGFR wt lung ADs [29]. The patients, TTF-1 positive or negative ADs, could benefit from the first-line chemotherapy [30].…”
Section: Villa Et Al Reported That the Most Common Histologic Type Smentioning
confidence: 94%
“…Many authors have studied the association between EGFR mutations and histologic type of Ads and TTF-1 expression, as well as pathologic stage of the disease [27,28,29,30].…”
Section: Other Recurrent Mutations In Exon 18-point Mutations In Posmentioning
confidence: 99%
“…показали, что экспрессия белка p63 -физиологического регулятора фенотипа стволовых клеток в сквамозном эпителии -распространенное явление при ПРЩЖ и АИТ, т.е. экспрессия p63 может выступать в качестве потенциального патобиологического связующего звена между этими двумя заболеваниями [8].…”
Section: иммунологические аспекты папиллярного рака щитовидной железы что нового?unclassified